Development of Adobe Flash Learning Media Based on Metacognitive Ability as a Learning Innovation during the Covid-19 Pandemic - Ina Nurhayati; Aripin Aripin; Khomsatun Ni'mah (IKIP Mataram, 2022)
This study aims to develop adobe flash learning media based on metacognitive abilities. The research method used is research and development (R&D) with the ADDIE model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation.This research was conducted at SMA Negeri 1 Bantarkalong in the odd semester of the 2021/2022 academic year. Limited trials were carried out on five students of class XII MIPA 1, and field tests were carried out on class XII MIPA 2, which amounted to 21 people. The validation results of material and media experts stated that the adobe flash learning media based on metacognitive abilities was valid and could be used with some improvements.Based on the questionnaire responses, the limited trial students scored 191 in the